Pengembangan Media Lumpur Lapindo Sebagai Bahan Tambah Pembuatan Keramik - Ridho Sampurno; Ilham Jangkit Pamuncak; Nova Eka Saputra; Yanatra Budi Pramana; Krisyanti Budipramana (Universitas PGRI Adi Buana Surabaya, 2023)
In making ceramics, several materials are needed, namely feldspar, silica, clay, and talc and go through several processes that are milling, casting, drying, dry body inspection, glazing and calcination. In order to get good rheology results, we must get quality ingredients. In the Lapindo mudflow, it is often likened to just a natural disaster and very few think about how to manage the mud. Lapindo mud there is a large amount of silica which might be used for making ceramics. To get pure silica in Lapindo mud it is necessary to carry out an extraction process.